Respon Pertumbuhan Tanaman Kangkung (Ipomoea reptans Poir) Varietas Bangkok LP-1 Secara Vertikultur Akibat Pemberian Limbah Air Kelapa (Cocos nucifera L.) - Nabila Nur Afifah; Hayatul Rahmi; Bastaman Syah (Peneliti.net, 2021)
This study aims to determine the growth response and yield of kangkung, Bangkok variety LP-1 due to the application of several concentrations of coconut water waste. This research was conducted in Gang Lebak Sari, Sukaluyu Village, Telukjambe Timur District, Karawang Regency, West Java Province at an altitude of 25 to 30 meters above sea level with a slope ranging from 5-15°. The study was carried out in March 2021-April 2021. This research method used a non-factorial Randomized Group Design (RAK) consisting of 12 treatments and 3 replications: concentration. 0% (A0-), 10% (A1), 20% (A2), 30% (A3), 40% (A4), 50% (A5), 60% (A6), 70% (A7), 80% (A8), 90% (A9), 100% (A10) and there is a positive control, namely A0+ (POC NASA 6ml/L as a comparison), so that there are 36 experimental units. The results showed that there was no significant effect of fermenting coconut water on the growth of kangkung (Ipomoea reptans Poir.) bangkok variety LP-1. In this study, the highest average value in the parameters of plant height, number of leaves, stem diameter, leaf area, wet weight and dry weight was treatment A0+ (POC NASA 6ml/L as comparison).